Literature Review Efektifitas Terapi Garam Terhadap Pengobatan Granuloma Umbilikalis - Fitriya, Wahida; Fitriani, Aice Bela; Diba, Farah; Rohmini, Samsi; Helma; Ida Sofiyanti (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Umbilical granuloma (UG) is a major problem in neonates and young babies. This usually occurs in mothers due to continuous leakage of secretions in the umbilicus area after separation. Delayed treatment of granulomas continues to flow and causes persistent irritation over a long period of time, up to weeks. Several management modalities for umbilical granuloma include; using cooking salt, granuloma ligation, uterization and surgical excision. Umbilical granuloma is granular tissue that grows prominently in the center of the navel after the baby's umbilical cord falls off. Umbilical granuloma is reported to occur in 1 in 500 newborns. A literature study was conducted to determine the effectiveness of salt therapy in treating umbilical granulomas. The criteria for the articles reviewed were articles within the year 2020-2023 and used the Google Scholar database. The keywords used are "Salt" and "Umbilical Granuloma" or "Salt" and "Umbilical Granuloma". The search results obtained 200 articles that matched the keywords with 95 articles that matched the topic and a review was carried out on 5 articles that met the inclusion and exclusion criteria. Based on the 5 articles reviewed, all articles discuss the effectiveness of salt therapy for treating umbilical granulomas although there are several differences in the application process. Treatment of umbilical granuloma with salt is very effective with cure rates reaching 56% - 100%, safe, without complications, cheap, easily available, and can be done by anyone.   Abstrak Granuloma Umbilikal (UG) merupakan masalah utama pada neonates dan bayi muda. Biasanya sering terjadi pada ibu karena adanya kebocoran secret yang terus menerus pada daerah umbilicus setelah pemisahan. Penanganan granuloma yang tertunda, tetap mengalir dan menyebabkan persisten iritasi dalam jangka waktu lama hingga berminggu-minggu. Beberapa modalitas manajemen dilakukan granuloma umbilikalis termasuk; menggunakan garam masak, ligase granuloma, keuterisasi dan bedah eksisi. Granuloma umbilikal adalah jaringan granular yang tumbuh menonjol di tengah pusar setelah tali pusat bayi terlepas. Granuloma umbilikal dilaporkan terjadi pada 1 dari 500 bayi baru lahir. Studi literatur dilakukan untuk mengetahui efektifitas terapi garam dalam upaya penanganan granuloma umbilikal. Kriteria artikel yang ditelaah adalah artikel dengan rentang tahun 2020-2023 dan menggunakan database Google Scholar. Kata kunci yang digunakan adalah “Salt” and “Umbilical Granuloma” atau “Garam” dan “Granuloma Umbilikal”. Hasil penelusuran didapatkan 200 artikel yang sesuai dengan kata kunci dengan 95 artikel yang sesuai dengan topik dan dilakukan telaah pada 5 artikel yang memenuhi kriteria inklusi dan eksklusi. Berdasarkan 5 artikel yang telah ditelaah, semua artikel membahas efektifitas terapi garam untuk mengobati granuloma umbilical meskipun terdapat beberapa perbedaan dalam proses pengaplikasiannya. Pengobatan granuloma umbilikal dengan garam sangat efektif dengan angka kesembuhan mencapai 56% - 100%, aman, tanpa komplikasi, murah, mudah tersedia, dan dapat dilakukan oleh siapapun.